(untitled) (Physical Education, Health and Social Sciences, 2025)
United nation developed the Goal of Sustainability and risk management is playing pivotal role through mitigating uncertainty and threats which are accord in financial, environmental, economical, and social systems. long-term sustainability development essential by effective risk management. This research paper exploring the risk management framework with Sustainability Development Goal, quantitative analysis provide empirical study assessing risk factors and their impact on SDGs, risk management strategies is fostering about climate change, financial in-stability and social-economics disparity. Statistical modeling analysis through Smart – PLS version 4 & SPSS version 25 Software. Total 400 Questionnaire distributed among the micro level business enterprises and gathered 317 which are suitable for data analysis, research’s Data analysis provides, risk assessment matrices and alleviate poverty. Results showing that the employees mixed method approach valuable due to incorporating regression analysis, findings explain proactive risk management approach positively enables sustainability development outcomes by reducing poverty and improve adapting capacity. This research also point-out policy implication to governments policy makers, corporations and international development organization to strengthen risks governance with align decision achieving sustainability objectives and goals. The study highlights best practices and innovative solutions for managing risks related to poverty, health, education, and environmental protection, ultimately contributing to a more resilient and sustainable future.